What Size Cerebral Aneurysms Rupture? A Systematic Review and Meta-Analysis of Literature. (1st September 2019) - Mokin, Maxim; Waqas, Muhammad; Gong, Andrew; Chin, Felix; Rai, Hamid; Vakharia, Kunal; Rajabzadeh Oghaz, Hamidreza; Snyder, Kenneth V; Davies, Jason; Levy, Elad I; Meng, Hui; Siddiqui, Adnan H
Abstract: INTRODUCTION: Size of the cerebral aneurysms is given a considerable weightage in deciding on the management for cerebral aneurysms. Literature on the size of ruptured aneurysms is heterogenous and often contradictory. The purpose of this systematic review was to determine the size of ruptured aneurysms with respect to location. METHODS: We conducted a systematic review of literature. The protocol was registered with PROSPERO. PubMed, Cochrane, CiNAHL, and EMBASE databases were reviewed All the studies reporting the mean size of consecutive patients with intracranial aneurysms were included. Studies that did not report mean with standard deviations or were restricted to the study of small or large aneurysms were excluded. Heterogeneity was assessed using I2 and random effect model was used to perform metanalysis of the data. Pooled mean and standard deviation were calculated for overall size and subgroup of aneurysms at a specific location. R statistical package was used for analysis. RESULTS: A total of 64 studies with 10 873 intracranial aneurysms were included in the meta-analysis. Pooled mean ruptured intracranial aneurysm size in 64 studies was 6.99 ± 4.14 mm. Mean size for anterior communicating artery was reported by 9 studies, 1118 aneurysms with a pooled mean of 4.65 ± 2.12 mm. Posterior communicating artery aneurysm size was reported in 10 studies with pooled mean of 6.43 ± 2.41 mm. Nine studies reported mean size of middle cerebral artery. The pooled value was 8.90 ± 4.91 mm. Pooled mean size for posterior inferior cerebellar artery was 4.09 ± 1.63 mm. CONCLUSION: Mean size of ruptured intracranial aneurysms reported by most studies is less than 7.0 mm and varies with the location of the aneurysm. Morphological and hemodynamic factors other than size may be more important in determining rupture risk.